Evaluación del sistema de control interno y su incidencia en la gestión de la ferretería “GÓMEZ” del cantón Valencia provincia de Los Ríos, año 2012 - Aguiar Tello, Melida Lourdes (2015)
The research was conducted at the hardware store "Gomez", located in the province of Los Ríos Region Valencia, Av. December 13, lasting four months, the proposed objectives were a) evaluate the internal control system and its impact on the management of Hardware "Gomez" Canton Valencia province of Los Ríos, 2012, b) Analyze the situation of internal control activities carried out on Administrative and Financial areas, c) Apply the questionnaires to determine the level confidence and control risk in each of the areas of hardware "Gomez", d) Issuing a general internal control report e) Propose the manual of procedures of internal control. The methodology applied was qualitative and quantitative, note that using the application of direct, indirect methods among others to describe problems in general to the particular and vice versa general conclusions and infer. Further field research was used because it was used for the implementation of internal control questionnaires according to the environments COSO control model I; and the preliminary recognition of the company through interviews and direct observation. Library research (books, theses, WESB) was also used to obtain the views of the different authors and theories for supporting the problem under study. The results allowed testing the hypothesis "The evaluation of internal control will determine the level of risk management is high on the Hardware" Gomez ", because the level of risk management is high and the area purchase, sales and inventory is medium and in the area of accounting is high, because you do not have manuals and administrative process, it lacks policies and code of ethics that help make possible good unemployment forge.